SIP-HTM based noro-virus sensor using virus-like particles - Tiainen, Jaana (2021)
Surface imprinted polymers (SIP) are biomimetic receptors that have active binding cavities on their surface, and that selectively bind particles similar with template particles used in the production process. SIPs can be synthesized in a few ways, and since 2001 SIPs have been used in many applications. When a SIP is coupled with a detection platform, it can act as a biosensor revealing the presence of small particles such as viruses. SIPs have been coupled with a quartz crystal microbalance (QCM), impedance spectroscopy, surface plasmon resonance and thermal methods. In the group of Prof. Patrick Wagner at KU Leuven, a heat transfer method (HTM) is being developed that observes the change in thermal conduction due to binding of the particles on the surface of the polymer.